A Key Intermediate in Copper‐Mediated Arene Trifluoromethylation, [nBu4N][Cu(Ar)(CF3)3]: Synthesis, Characterization, and C(sp2)−CF3 Reductive Elimination. Issue 25 (13th May 2019) - Lu, Zehai; Liu, He; Liu, Shihan; Leng, Xuebing; Lan, Yu; Shen, Qilong
Abstract: The synthesis, characterization, and C(sp 2 )−CF3 reductive elimination of stable aryl[tris(trifluoromethyl)]cuprate(III) complexes [ n Bu4 N][Cu(Ar)(CF3 )3 ] are described. Mechanistic investigations, including kinetic studies, studies of the effect of temperature, solvent, and the para substituent of the aryl group, as well as DFT calculations, suggest that the C(sp 2 )−CF3 reductive elimination proceeds through a concerted carbon–carbon bond‐forming pathway. Abstract : Mechanism of elimination : The synthesis, characterization, and C(sp 2 )−CF3 reductive elimination of stable aryl[tris(trifluoromethyl)]cuprate(III) complexes [ n Bu4 N][Cu(Ar)(CF3 )3 ] are reported. Kinetic studies, investigations of temperature and solvent effects, and DFT calculations indicate that C(sp 2 )−CF3 reductive elimination proceeds through a concerted bond‐forming pathway.